24 Association between novel cardiopulmonary exercise testing indices and stage B Heart Failure in people with Type 2 Diabetes. (28th January 2023) - Walters, Grace; Gulsin, Gaurav S; Redman, Emma; Henson, Joseph; Argyridou, Stavroula; Yates, Thomas; Davies, Melanie J; Parke, Kelly; McCann, Gerry P; Brady, Emer M
Abstract : Introduction: Asymptomatic people with Type-2 Diabetes (T2D) have reduced exercise capacity and are at high risk of developing heart failure (HF) with evidence of adverse cardiac remodelling (Stage-B HF). We sought to determine whether novel cardiopulmonary exercise testing (CPET) indices were independently associated with Stage B HF in T2D. Materials and Methods: Obese working-age asymptomatic adults with T2D with no known cardiovascular disease and healthy volunteers (HV) were prospectively enrolled and underwent echocardiography, stress-perfusion cardiac MRI (CMR), and a symptom-limited incremental CPET as part of the DIASTOLIC study (NCT02590822 ). Adjusted linear regression (for age, sex, and smoking status) was used to assess independent associations between each CPET measure (VE/VCO2, VO2 recovery (VO2Rec), HR recovery (HRRec), HR reserve (HRRes), VO2 at ventilatory threshold (VO2VT) with, left ventricular (LV) mass: volume, peak early diastolic strain rate (PEDSR), echocardiographic E/e', mean aortic distensibility [AoD], and myocardial perfusion reserve (MPR). Results: Eighty-five people with T2D and 36 HVs were included and well matched for age, sex, and ethnicity. Those with T2D had higher body weight, BMI, bloodpressure, heart rate, E/e', concentric remodelling and reduced diastolic strain rate. All CPET and CMR measures were worse in T2D vs HV: VO2VT 9.06 vs 13.32ml/kg/min; VO2Rec17.71 vs 20.36%, HRRec12.26 vs 6.27% HRRes 103.62 vs 154.86%, all p-value <0.001; E/e' 8.26 vs 6.42, LV mass: volume 0.83 vs 0.71, AoD 4.14 vs 6.56, PEDSR 1.00 vs 1.10, MPR 3.03 vs 3.98, all p-value <0.01. Independent associations were found between CPET and CMR: VO2VT and MPR (β=0.273), HRRec and AoD (β=0.222), all p-value <0.01 after Bonferroni correction Discussion: Novel CPET makers show stronger or additive prognostic power to peak VO2 in HF and may be more reliable e.g., VO2VT <11 is reportedly 2.7-fold better at predicting 6-month mortality than VO2peak, 1 and while HRRec provides equal prognostic power it can be obtained sub-maximally. 2 Further longitudinal studies are required to determine clinical relevance in asymptomatic T2D. Conclusion: Multiple novel CPET markers were independently associated with adverse cardiac remodelling on MRI and may be useful for risk stratification in T2D. Acknowledgements: Funding NIHR Research Trainees Coordinating Centre through a career development fellowship to G.P.M. (CDF 2014–07–045) the British Heart Foundation through a Clinical Research Training Fellowship (FS/16/47/32190). References: Gitt AK, et al . Exercise anaerobic threshold and ventilatory efficiency identify heart failure patients for high risk of early death. Circulation, 2002;106 (24):3079–3084. Cahalin LP, et al . The prognostic significance of heart rate recovery is not dependent upon maximal effort in patients with heart failure. International Journal Of Cardiology, 2013;168 (2):1496–1501.